Mental health services for children exposed to armed conflict: Médecins Sans Frontières' experience in the Democratic Republic of Congo, Iraq and the occupied Palestinian territory. (1st November 2013) - Lokuge, K; Shah, T; Pintaldi, G; Thurber, K; Martínez-Viciana, C; Cristobal, M; Palacios, L; Dear, K; Banks, E
Abstract : Background: Armed conflict has broad-ranging impacts on the mental health and wellbeing of children and adolescents. Mental health needs greatly exceed service provision in conflict settings, particularly for these age groups. The provision and targeting of appropriate services requires better understanding of the characteristics and requirements of children and adolescents exposed to armed conflict. Methods: Routine patient and programme monitoring data were analysed for patients <20 years of age attending mental health services provided by Médecins Sans Frontières (MSF) in three countries affected by armed conflict: the Democratic Republic of Congo (DRC), Iraq and the occupied Palestinian territory (oPt). The demographic characteristics, presenting mental health complaint, attributed precipitating event, services provided and short-term outcomes for mental health services users in each country are described. Results: Between 2009 and 2012, 3025 individuals <20 years of age presented for care in DRC and Iraq, and in 2012 in oPt, constituting 14%, 17·5% and 51%, respectively, of all presentations to MSF mental health services in those three countries. The most common precipitating event was sexual violence in DRC (36·5%), domestic violence in Iraq (17·8%) and incarceration or detention in oPt (33%). Armed conflict-related precipitants were reported by 25·9%, 55·0% and 76·4% of youths in DRC, Iraq and oPt, respectively. The most common presenting complaints in children and adolescents were anxiety-related, followed by mood-related, behaviour-related and somatisation problems; these varied according to country and precipitating event. Although a high proportion (45·7%) left programmes early, 97% of those who completed care self-reported improvement in their presenting complaint. Conclusions: Brief trauma-focused therapy, the current MSF mental health therapeutic intervention, appears to be effective in reducing symptoms arising from the experience of trauma. Although inferences on outcomes are limited by high default rates, this provides a feasible tool for addressing the mental health needs of children exposed to armed conflict. Priorities for future research include understanding why children and adolescents constitute a small proportion of patients in some programmes, why many leave care early and how to address these issues, but this research must occur within the context of efforts to provide access to mental health services for children.